Role of parenting attitudes and basic psychological needs in life skills development and transfer among Korean student-athletes - Dong-Su Kim; Hyeongho Jin; Junsu Bae (Scientific Reports)
Abstract Recent literature on positive youth development through sports has consistently emphasized the role of parents in developing and transferring life skills of athletes. However, related research findings are still lacking, especially within Asia. This study aimed to validate a structural relationship of perceived positive and negative parenting attitudes, basic psychological needs, life skills development, and transfer among student-athletes in South Korea. A survey was conducted with 355 high school athletes aged 16 to 18 (263 males and 92 females; average age 17.04) registered with the Korea Olympic Committee. They participated in 10 different sports, including Taekwondo, soccer, baseball, basketball, badminton, and swimming. Structural equation model analysis was conducted to examine hypotheses. The research results showed that positive parenting attitudes directly predicted basic psychological needs and life skill development, and indirect effects were also confirmed. On the other hand, negative parenting attitudes directly predicted a negative impact on life skill development, but no indirect effects were found. Finally, life skill development positively predicted transfer. These results demonstrate that parents play a direct or indirect role in the development and transfer of life skills among student-athletes by satisfying their basic psychological needs.